2013
DOI: 10.1007/s10822-012-9628-0
|View full text |Cite
|
Sign up to set email alerts
|

EuLoc: a web-server for accurately predict protein subcellular localization in eukaryotes by incorporating various features of sequence segments into the general form of Chou’s PseAAC

Abstract: The function of a protein is generally related to its subcellular localization. Therefore, knowing its subcellular localization is helpful in understanding its potential functions and roles in biological processes. This work develops a hybrid method for computationally predicting the subcellular localization of eukaryotic protein. The method is called EuLoc and incorporates the Hidden Markov Model (HMM) method, homology search approach and the support vector machines (SVM) method by fusing several new features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…StDof putative bipartite NLS showed two basic regions (B1 and B2) separated by a long spacer segment 17 amino acids long similar to the previously mapped bipartite NLS (Krebs et al, 2010). The protein subcellular localization prediction tool, EuLoc (Chang et al, 2013) showed that all StDof proteins are localized to the nucleus without exception.…”
Section: Conserved Motif Analysis Of Stdof Proteinsmentioning
confidence: 55%
See 1 more Smart Citation
“…StDof putative bipartite NLS showed two basic regions (B1 and B2) separated by a long spacer segment 17 amino acids long similar to the previously mapped bipartite NLS (Krebs et al, 2010). The protein subcellular localization prediction tool, EuLoc (Chang et al, 2013) showed that all StDof proteins are localized to the nucleus without exception.…”
Section: Conserved Motif Analysis Of Stdof Proteinsmentioning
confidence: 55%
“…Potatospecific StDof protein domains were searched against the PROSITE database (http://prosite.expasy.org/) for protein domains with known functions (Sigrist et al, 2013). Subcellular localization of the StDof proteins was predicted using the EuLoc protein localization prediction web server (Chang et al, 2013).…”
Section: Phylogenetic Analysis and Identification Of Conserved Motifsmentioning
confidence: 99%
“…Only the jackknife test is the least arbitrary that can always yield a unique result for a given benchmark dataset. Therefore, the jackknife test has been widely recognized and increasingly adopted by investigators to examine the quality of various predictors (see, e.g., [42, 58, 59, 62, 64, 66, 67, 70, 103107]). Therefore, in this study, the jackknife test was also used to examine the performance of the predictor.…”
Section: Resultsmentioning
confidence: 99%
“…With the aid of kernel function, a non-linear classification problem in a low dimension space can be transformed to a linear one after mapped it to a high dimension space. Recently, algorithms based on SVM are emerged massively [19,20].…”
Section: A Basic Machine Learning Algorithmsmentioning
confidence: 99%